Bioethics and the Failure of Success - Koch, Tom (British Journal of Healthcare and Medical Research, 2025)
Since its inception in the 1970s Bioethics has become the dominant perspective on issues of medical care and organization. It has done so with the declaration that neither the traditional Hippocratic ethic nor ethicists grounded in religious perspectives should have a similar posture in debate over medical dilemmas in modern, post-industrial society. It has failed, however, to offer convincing answers to a range of issues arising in both the evolving medical science and the realities of medical practice. While acknowledging its strength an understanding of its failures may permit a better and more comprehensive and humanistic medical ethics to be presented.